Economy Media Strategy of Kompas TV Facing Digital Era - Praditha, Anastasia; Widodo, Ari (Journal of Communication and Public Relations, 2022)
The transition from analog television to digital is not the end of television evolution. People no longer consume traditional media as much as they did in the past, moreover audience members are more empowered than at any other time in media history. Audience members no longer just consume content—they can also make content in a multitude of ways, whether through blogging, podcasting, uploading videos, or social networking. The market became the determinant of the death of the media industry. This condition allows the industry to become “cannibal”. Media industry must be supported by strong capital for infrastructure, highly competitive human resources (professional for production and distribution) and professional management. The amount of advertising spend are affected. The growth of advertising spends in 2017 were positive but slowly, it decreased by 2%. Ad spending has a downward trend, in 2017 growth was only 8% compared to the previous year’s growth of 20%. The way Kompas discover this challenge by set a new strategy, known as economy media theory. Media economics referred to business operation and financial activities of companies that produce and sell their products to media industries.